2016
DOI: 10.3390/s16060857
|View full text |Cite
|
Sign up to set email alerts
|

Field Measurements and Numerical Simulations of Temperature and Moisture in Highway Engineering Using a Frequency Domain Reflectometry Sensor

Abstract: This paper presents a systematic pioneering study on the use of agricultural-purpose frequency domain reflectometry (FDR) sensors to monitor temperature and moisture of a subgrade in highway extension and reconstruction engineering. The principle of agricultural-purpose FDR sensors and the process for embedding this kind of sensors for subgrade engineering purposes are introduced. Based on field measured weather data, a numerical analysis model for temperature and moisture content in the subgrade’s soil is bui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 34 publications
0
12
0
1
Order By: Relevance
“…is study was being performed to investigate the moisture migration of the new embankment, and the best combination method to keep the volumetric moisture content stability was found. e VADOSE/W module of the Geo-Studio 2007 Software (GEOSLOPE International Ltd., Canada) [23] was used to calculate the water infiltration into two layers of soils with contrasting particle sizes.…”
Section: Numerical Simulationsmentioning
confidence: 99%
See 1 more Smart Citation
“…is study was being performed to investigate the moisture migration of the new embankment, and the best combination method to keep the volumetric moisture content stability was found. e VADOSE/W module of the Geo-Studio 2007 Software (GEOSLOPE International Ltd., Canada) [23] was used to calculate the water infiltration into two layers of soils with contrasting particle sizes.…”
Section: Numerical Simulationsmentioning
confidence: 99%
“…Hatami et al [22] investigated the seasonal change of the humidity field of embankments. Yao et al [23] found that the volumetric moisture content of the new embankment increases significantly through FDR sensors and simulation. However, they only thought that the increase in the humidity of the new embankment was due to the moisture migration between the embankment and the surrounding atmosphere.…”
Section: Introductionmentioning
confidence: 99%
“…erefore, a rapid method to determine the water content is the key to calculate the degree of compaction using (1). e water content of subgrade slope soil can be calculated using the numerical simulation, which is proved to be rational by some researchers using the Geo-Studio software [22][23][24][25].…”
Section: Degree Of Compaction According To Numerical Moisture Contentmentioning
confidence: 99%
“…en, a numerical modelling of the subgrade slope of K24 + 600 was completed according to the method of the literature [22,26,27]. Water content was calculated using the parameters mentioned above, and the results of calculated water content values of soil are shown in Figure 9.…”
Section: Calculated and Measured Water Content Valuesmentioning
confidence: 99%
“…Zum Wasserhaushalt von Straßendämmen lagen bis dato nur vergleichsweise wenige Ergebnisse experimenteller Untersuchungen vor. Diese beschäftigten sich in erster Linie mit der Entwicklung von Wassergehalten in Straßendämmen ohne die Sickerwassermengen zu erfassen und zu quantifizieren . Zur gezielten Analyse des Wasserhaushalts von Straßenböschungen wurden deshalb bei der Bundesanstalt für Straßenwesen (BASt) Lysimeteruntersuchungen an Ausschnitten von Straßendämmen durchgeführt.…”
Section: Introductionunclassified